Pengaruh Kualitas Audit, Profitabilitas, Opini Audit, Dan Ukuran Perusahaan Terhadap Audit Delay Dengan Pajak Terutang Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Aurelia, Felicia; Beatrice, Angela; Teng, Sauh Hwee; Hantono, Hantono (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the effect of audit quality, profitability, audit opinion, and company size on audit delay, with taxes payable as a moderating variable. The study population includes 14 companies in the pharmaceutical sub-sector during the period 2019-2024, and 8 companies were selected as samples using purposive sampling. Data analysis was conducted using moderation regression. The results show that only profitability has a significant effect on audit delay, while audit quality, audit opinion, company size, and taxes payable do not show a significant effect. Furthermore, the moderation test reveals that taxes payable only strengthen the effect of profitability on audit delay, but do not moderate the relationship between audit quality, audit opinion, and company size with audit delay.